2014
DOI: 10.5604/15093492.1097490
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Fracture in Osteosarcoma: Is it Always an Indication for Amputation?

Abstract: 1. A pathologic fracture in an OS is not always a contraindication for limb salvage because the oncologic results are acceptable. 2. In selected cases limb salvage has similar success rates to amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…They attributed this to tumor dissemination. However, other investigators reported no decrease in overall survival in pathologic fracture patients . Our results agree with the latter studies.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…They attributed this to tumor dissemination. However, other investigators reported no decrease in overall survival in pathologic fracture patients . Our results agree with the latter studies.…”
Section: Discussionsupporting
confidence: 93%
“…However, other investigators reported no decrease in overall survival in pathologic fracture patients. 7,16,21,24,25 Our results agree with the latter studies. There was no significant difference between the final outcomes in patients with a pathologic fracture and those without.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Twenty-four articles were assessed for eligibility criteria. Twenty-one studies met our eligibility criteria and were finally included in our meta-analysis [1, 3, 4, 6-9, 13-16, 19, 22, 24-26, 29-32, 34].…”
Section: Methodsmentioning
confidence: 99%